Variability of the Caribbean low‐level jet during boreal winter: large‐scale forcings. (4th September 2015) - Maldonado, Tito; Rutgersson, Anna; Amador, Jorge; Alfaro, Eric; Claremar, Björn
ABSTRACT: An index capturing the anomalies of the zonal wind at 925 hPa from 1950 to 2010 was defined to explore the relationship between the fluctuations of the Caribbean low‐level jet (CLLJ) and the main climate variability modes affecting the Intra‐Americas Sea Region. El Niño Southern Oscillation (ENSO) events, here defined using the Niño 3.4 index, are found to be the most important variability modes for the jet anomalies, in agreement with previous studies. However, the Pacific Decadal Oscillation (PDO) and the Pacific/North American (PNA) teleconnection pattern also show significant correlations with the CLLJ anomaly index during February. The North Atlantic Oscillation (NAO) and the Arctic Oscillation (AO) reveal a possible interaction with the jet anomalies that could be connected with the cold fronts and cold air surges arriving to the Caribbean basin from the Northern Hemisphere during winter. A composite technique is used to explain the correlations with the Pacific indexes. We found that ENSO events are connected to CLLJ anomalies by modulating the sea‐level pressure (SLP) near the east coast of the United States and the Aleutian Low. The pattern displayed by the SLP anomalies (SLPa) is also associated with the PNA. During warm (cold) ENSO phases, negative (positive) anomalies in the SLP field over the east coast of North America produce cyclonic (anticyclonic) circulations at low levels. However, the ENSO signal in the SLPa and the PNA pattern are modulated by the phases of the PDO. Results indicate that when the ENSO and PDO are in phase (out of phase), the SLPa signal is enhanced (weakened or cancelled), affecting the CLLJ anomalies in both direction and intensity, also changing the spatial distribution of precipitation.